Territorial and marketing strategies related to religious tourism in Northern Moldavia, Romania - Bogdan-Constantin Ibănescu; Alina Munteanu; Oana Mihaela Stoleriu (CES Working Papers, 2018)
Religious tourism represents an important segment of the present Romanian tourism market, with monasteries being constantly well ranked in the preferences of foreign or domestic visitors. Every year the number of religious tourists and pilgrims in Romania is increasing, as well as the number of religious events. In this context, religious destinations try to adapt to a dual orientation of the visitors' interests and practices: cultural tourism and pilgrimage. This study aims to identify patterns in the strategies aiming to attract pilgrims and/or tourists, in reaction to an increasing national and regional competition. By mapping the results, specific spatial structures were identified, in relation with this dichotomy of practices and communication strategies. Major pilgrimage destinations demonstrate a remarkable adaptability of the experiences and services provided to tourists, while famous cultural and religious destinations tend to delocalise their marketing strategies towards regional and national institutions and tourism agencies.
Keywords: 330; religious tourism; pilgrimage; marketing strategy; Romania